Antiradical properties of peptides from hydrobionts - E. P. Karaulova; T. N. Slutskaya; E. V. Yakush (Известия ТИНРО)
Antiradical activity of water-soluble components of tissues is investigated for 26 species of marine organisms belonged to 7 classes: Bivalvia, Cephalopoda, Malacostraca, Holothuroidea, Asteroidea, Echinoidea, and Actinopterygii. Molecular weight of the proteins and peptides was measured in the water extracts using the modular liquid chromatograph (Agilent Technologies 1260 Infinity, USA) with UV detection at 280 nm in TSK gel column G 3000PWXL 7.8 mm I.D. × 30 cm (TOSOH Corporation, Japan) under flow rate of 0.3 mL/min and temperature of 25о C. All samples were twice prepared and double measured. The mobile phase consisted of 0.1 N NaCI 20 mM Tris-HCI buffer with pH 7.8. The following standard protein samples were used as a reference for the molecular weight measurement: bovine serum albumin (MW 66.3 kDa), egg albumin (44.3 kDa), myoglobin (18.0 kDa), cytochrome C (12.4 kDa), aprotinin (6.5 kDa), and bacitracin (1.4 kDa) (Sigma-Aldrich Co., USA). All samples were filtered before injection through 0.2 µm syringe filter (Whatman, PVDF). Molecular weight of peptides was calculated by the elution time. Scavenging effect on DPPH free radical was measured by Molyneux method and on ABTS radical – by the method proposed by Re et al. The maximum antiradical activity (measured by mg of ascorbic acid per 1 g) was found for the tissue of Patiria pectinifera (5.21), its various values were determined for the tissue of bivalve mollusks (Corbicula japonica, Mercenaria stimpsoni, Spisula sachalinensis, and Glycymeris yessoensis — 5.10; 1.15; 1.36 and 1.08, respectively) and medium values — for gonads of Strongylocentrotus intermedius and S. nudus (2.18 and 2.21, respectively). The amount of proteins and peptides with low molecular weight (1–5 kDa) correlated well with the radical scavenging activity (Pearson correlation coefficient 0.801, r2 = 0.642).